The role of GABAB receptors in the subcortical pathways of the mammalian auditory system - Tureček, Rostislav; Melichar, Adolf; Králíková, Michaela; Hrušková, Bohdana (Frontiers in Endocrinology, 2023)
GABAB receptors are G-protein coupled receptors for the inhibitory neurotransmitter GABA. Functional GABAB receptors are formed as heteromers of GABAB1 and GABAB2 subunits, which further associate with various regulatory and signaling proteins to provide receptor complexes with distinct pharmacological and physiological properties. GABAB receptors are widely distributed in nervous tissue, where they are involved in a number of processes and in turn are subject to a number of regulatory mechanisms. In this review, we summarize current knowledge of the cellular distribution and function of the receptors in the inner ear and auditory pathway of the mammalian brainstem and midbrain. The findings suggest that in these regions, GABAB receptors are involved in processes essential for proper auditory function, such as cochlear amplifier modulation, regulation of spontaneous activity, binaural and temporal information processing, and predictive coding. Since impaired GABAergic inhibition has been found to be associated with various forms of hearing loss, GABAB dysfunction could also play a role in some pathologies of the auditory system.